2011
DOI: 10.1135/cccc2011075
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical preparation of poly(vinylferrocenium)perchlorate-polyaniline composite-modified platinium electrode in methylene chloride

Abstract: A new surface based on poly(vinylferrocenium)perchlorate-polyaniline (PVF + ClO 4 --PANI)composite-modified platinum electrode was prepared electrochemically to combine the electrocatalytic properties of an intrinsically conducting polymer and a redox polymer. The composite film was synthesized as a bilayer from individual polymerization solutions. Furthermore, PVF + ClO 4 -and PANI polymers were simultaneously deposited as a mixture from a methylene chloride solution containing PVF polymer and aniline monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…PVF + –PANI composite‐coated electrode was electrochemically prepared by codepositing PANI and PVF + polymers on Pt electrode in a methylene chloride solution containing PVF polymer, aniline monomer, and HClO 4 . Supporting Information, Figure S1 shows the cyclic voltammetric scans taken during deposition in the potential region between 0.20 and 1.80 V [versus Ag/AgCl (sat)].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PVF + –PANI composite‐coated electrode was electrochemically prepared by codepositing PANI and PVF + polymers on Pt electrode in a methylene chloride solution containing PVF polymer, aniline monomer, and HClO 4 . Supporting Information, Figure S1 shows the cyclic voltammetric scans taken during deposition in the potential region between 0.20 and 1.80 V [versus Ag/AgCl (sat)].…”
Section: Resultsmentioning
confidence: 99%
“…The green‐colored PVF + ( ClO4) redox polymer was synthesized on Pt disc electrode in methylene chloride solution containing 100 mmol L −1 TBAP/1.0 mg mL −1 of PVF using potentiodynamic method. When the potential range was applied from −0.20 to 1.80 V [versus Ag/AgCl (sat)], green‐colored PVF + ( ClO4) film was not observed on Pt electrode because of its reduction to PVF and thus being stripped from the electrode surface by dissolution in methylene chloride . Nevertheless, the green PVF + ( ClO4) film can be easily obtained on Pt disc electrode surface when the lower potential is chosen as 0.20 V instead of −0.20 V .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kavanoz et al reported composite film of PANI with poly(vinylferrocenium) perchlorate on Pt electrode in dichloromethane medium. 9 Another widely used conductive polymer is poly(3-methylthiophene) (P3MT) that can be directly synthesized on electrode surface by electrochemical polymerization of 3-methylthiophene. Synthesis of P3MT for modification of electrodes were reported in acetonitrile, 6,10 dichloromethane, 4 chloroform 11 and aqueous solution 12 and prepared P3MT modified electrodes have shown electrocatalytic effect on riboflavin, 13 some phenolics 14,15 and dopamine.…”
Section: Introductionmentioning
confidence: 99%